1999
DOI: 10.1046/j.1365-2672.1999.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of hospital waste sludge using hypochlorite and chlorine dioxide

Abstract: C .-T. T SA I A N D S .-T . L IN . 1999. Hypochlorite and chlorine dioxide were used to disinfect hospital waste-water sludge. Their abilities to inactivate pathogenic microorganisms were compared. Reductions in indigenous coliform organisms and Pseudomonas aeruginosa were estimated. The results indicate that hypochlorite is a better disinfectant than chlorine dioxide for coliforms. Higher disinfection efficiency was obtained by treating a lower concentration of sludge. In addition, a higher agitation speed ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
1
12
0
3
Order By: Relevance
“…This important consumption in water of hospitals gives significant volumes of wastewater loaded with microorganisms, heavy metals, toxic chemicals and radioactive elementsP [4] P.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This important consumption in water of hospitals gives significant volumes of wastewater loaded with microorganisms, heavy metals, toxic chemicals and radioactive elementsP [4] P.…”
Section: Resultsmentioning
confidence: 99%
“…If the final effluent is discharged into coastal waters close to shellfish habitats, disinfection of the effluent will be required throughout the year. To stop the phenomenon of excess load in the process of the wastewater treatment plant, it seems important to consider upstream treatments to hospital wastewater before their discharge in the municipal sewage systemP [4] P.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorine dioxide is used as an alternative disinfectant because it does not form halogenated by-products, and is better than or equivalent to chlorine in the bactericidal effects and more remarkable than that of chlorine as a virucide in a wider pH range (Li et al, 1996Taylor and Butler, 1982b;Huang et al, 1997). However, Tsai and Lin (1999) reported that hypochlorite was better in inactivating E. coli in hospital wastewater and sludge than chlorine dioxide. This study also suggested that in terms of inactivating E. coli, f 2 phage and SARS-CoV, chlorine is better than chlorine dioxide.…”
Section: Discussionmentioning
confidence: 99%
“…This ability makes it useful to a lot of kind of uses: a drinking water disinfections; bleaching textiles; antimicrobial applications (United States Environment Protection Agency (USEPA), 2000). Some studies had related its use in disinfection of municipal wastewater (Dernat & Pouillot, 1992;Tsai & Lin, 1999) and the evaluation of its efficiency (Junli, Li, Nanqi, Fang, & Li, 1997a;Junli et al, 1997b).…”
Section: Introductionmentioning
confidence: 99%